Incidence of anterior knee pain post total knee arthroplasty in correlation with body mass index - Kanagarajah, Ganesha Devan (2022)
Introduction Anterior knee pain (AKP) post total knee arthroplasty (TKA) is believed to be multifactorial in aetiology with reported incidence of up to 40%. Body mass index (BMI) as a contributing factor to this complication has given mixed results based on previous studies. Given the increasing number of TKA cases done annually and in line with the rising number of overweight and obese populations in Malaysia, we would like to determine if there is a correlation between these two factors. Methodology A retrospective cohort study was done to analyse the 78 primary knee arthroplasties without patella resurfacing done in Hospital Universiti Sains Malaysia (HUSM) from 2018 to 2020. Incidence of AKP up to one year post arthroplasty and its correlation with BMI groups and other potential variables were analysed for any significant correlation. Statistical analysis was done using IBM SPSS Statistics Version 25. Results There were 22 male and 49 female patients with a mean age of 65.4 years. The incidence of AKP in this study was 5.1% which is relatively lower than average compared to other studies. The mean BMI was 29.6kg/m2 and patients were divided into two groups, first group with normal BMI and second group with overweight & obese BMI. There was no significant correlation between the two BMI groups and incidence of anterior knee pain, however all four patients with AKP were in the overweight group and female. Conclusion Anterior knee pain remains a challenging complication post total knee replacement with many factors (patient, implant, surgical techniques) still being heavily debated and studies continue to show mixed results. Although no correlation was found, we strongly recommend our patients to optimize BMI before surgery to reduce the risk of complications as 5.1% of patients with anterior knee pain were all in the overweight group. This is also to reduce other complications which are better established and to better optimize their comorbidities as well as general health prior to arthroplasty. Given the multifactorial cause of AKP, early identification and thorough assessment on a case-to-case basis is recommended to direct individualized patient management until a clear guideline on its prevention & management is established.